Induction chemotherapy and concurrent chemoradiotherapy for larynx preservation in laryngeal and hypopharyngeal cancer - Strojan, Primož (Radiology and oncology (Ljubljana), 2025)
To test the hypothesis that clinical tumor response after a single cycle of induction chemotherapy (ICT) can reliably differentiate between chemo-/radiosensitive and resistant tumors in the larynx preservation setting. Patients and methods Treatment consisted of docetaxel/cisplatin/5-fluorouracil (TPF) ICT followed by concurrent chemoradiotherapy (cCRT) with weekly cisplatin. The response of the primary tumor was assessed by transnasal endoscopy after the first ICT cycle. Results 37/39 (95%) patients with laryngeal (46%) or hypopharyngeal (54%) carcinoma responded to one cycle of ICT, and two patients were referred for salvage surgery. Laryngectomy-free survival at 2 and 5 years was 87% and 75%, respectively. The corresponding rates for locoregional control (and also for disease-free survival) were 79% and 70% and for overall survival 92% and 82%. Conclusions Clinical assessment of tumor response to one cycle of TPF ICT serves as a valid and easy-to-use predictor of tumor sensitivity to platinum-based cCRT.
Keywords: arynx preservation; chemoradiotherapy; induction chemotherapy; indukcijska kemoterapija; kemoradioterapija; ohranitev grla